ASSESSMENT OF THE INCIDENCE AND PREVALENCE OF DRY EYES IN DIABETIC INDIVIDUALS AND IT’S EFFECT ON VISUAL ACUITY - K., MIDHUNA; N., DIVYA; VEERAMANI, V. PANIMALAR A.; BHASKARAN, BINDU (International Journal of Current Pharmaceutical Research, 2020)
Objective: To find out the incidence and prevalence of Dry Eyes in Diabetic patients and find out its effect on visual acuity. Methods: A prospective study was conducted in Saveetha Medical College and Hospital. Schirmer’s test was done for 100 diabetic patients taking part in the research. Those with dry eyes were tested for their visual acuity and were asked to fill a questionnaire based on associated ocular symptoms. The collected data were analysed using Microsoft Excel. Results: There is about an incidence of 82% of dry eyes in diabetic patients. It’s more prevalent among elderly women. There seems to be a significant effect of dry eys on visual acuity as 31% of those tested with dry eyes have a moderate visual impairment. Conclusion: People with diabetes are at a higher risk of developing dry eye. So diabetic patients should undergo regular ocular examination and must be screened for dry eyes. Early diagnosis and treatment of dry eyes is the best choice to prevent ocular complications in the future.